The Significance of Elevated sST2 in Children with Kawasaki Disease - Zhaohua Yang; Yunming Xu; Yanqiu Chu; Jinghao Li; Hong Wang (Children, 2025)
Objectives: Kawasaki Disease (KD) is an acute vasculitis associated with systemic inflammation. This study aimed to investigate the level and clinical significance of soluble ST2 (sST2) in children with KD. Methods: A retrospective analysis was conducted on 287 pediatric KD patients treated at the Pediatric Cardiology Department of Shengjing Hospital, China Medical University, from November 2021 to December 2022. Patients were stratified into subgroups based on the presence of myocardial damage (MD), coronary artery lesions (CAL), multi-organ involvement (MOD; ≥3 organs) and/or intravenous immunoglobulin-resistant KD (IVIG-R KD). In each group, we analyzed the correlation between sST2 levels and various laboratory parameters, including white blood cell count (WBC), hemoglobin (HB), platelet count (PLT), C-reactive protein (CRP), interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR), N-terminal pro-brain natriuretic peptide (NT-pro BNP), D-dimer, and albumin (ALB). Results: Patients in the CAL group were significantly younger and predominantly male (p < 0.05). In the MD, CAL, MOD, and IVIG-R KD groups, levels of sST2, CRP, NT-pro BNP, and D-dimer were significantly higher than in their respective comparison groups (p < 0.05). sST2 showed weak positive correlations with WBC, CRP, IL-6, NT-pro BNP, and D-dimer, and weak negative correlations with HB and ALB (p < 0.05). sST2, HB, and IL-6 were identified as independent risk factors for MOD (p < 0.05). sST2 and HB were independent risk factors for IVIG-R KD (p < 0.05). Among acute-phase patients, four cases had sST2 levels > 200 ng/mL—all were classified as IVIG-R KD and MOD; three of these also developed coronary artery aneurysms (CAA). Conclusions: Elevated sST2 levels in the acute phase of KD may serve as a clinical indicator of IVIG-R KD, CAA, MOD, and MD.